Front Cover: Simultaneous determination of the herbicide bixlozone and its metabolites in plant and animal samples by liquid chromatography–tandem mass spectrometry. Issue 4 (19th February 2021) - Li, Congdi; Chen, Zenglong; Qin, Dongmei; Liu, Rong; Li, Li; Li, Wei; He, Yujian; Yuan, Longfei
Abstract : DOI: 10.1002/jssc.202000992 The cover picture shows an analytical method for simultaneous determination of the novel herbicide bixlozone and its metabolites in plant and animal samples. We have investigated the extraction and purification procedures, chromatographic conditions, and mass spectrometer parameters to obtain the optimal sensitivity. The satisfactory validation criteria and application to real samples suggest that the proposed methodology is a reliable multiresidue analytical method to trace four target compounds in seven food matrices, which include tomato, cucumber, apple, wheat flour, milk, meat, and egg.